Introduction : brain science : inside out - Cheah, Pike See (Universiti Putra Malaysia Press, 2016)
BRAIN – remains as the most sophisticated organ in the known universe. While more has been learned about it in the past two hundred years, we are still at a very early stage in our understanding. The field of Neuroscience is still in its infancy, but is rapidly exploding – turning many yesterday’s brain “myth” to today’s brain “facts”.